Application of chromosomal microarray in fetuses with increased nuchal translucency. (18th May 2020) - Zhao, Xin-Rong; Gao, Li; Wu, Yi; Wang, Yan-Lin
Abstract: Objective: To evaluate submicroscopic chromosomal abnormalities in fetuses with increased nuchal translucency (NT) and normal karyotype. Methods: A total of 319 fetuses with increased NT (≥3.0 mm) were tested using conventional karyotyping. When cytogenetic analysis showed normal chromosomes, the parents then received a consultation for chromosomal microarray (CMA) analysis, and a subsequent morphology scan was performed between 20 and 24 weeks gestation. Submicroscopic chromosomal abnormalities were assessed and compared between the fetuses with and without structural defects. Likewise, the prevalence of pathologic copy number variants (CNVs) among cases with increased NT was compared with the 926 low-risk cases consisted of patients whose sole indication for testing was advanced maternal age. Results: Chromosomal abnormality was identified in 32.29 (103/319) of fetuses, and 137 samples were tested using CMA. Additional pathogenic copy number variants (CNVs) were also detected in 5.12% (7/137) of the fetuses. There was no significant difference in the abnormal detection rate between fetuses showing an abnormal morphology scan and those with a normal morphology scan (11.11% [2/18] versus 4.20% [5/119], respectively; p > .05). The prevalence of pathological CMA results in cases with increased NT was significantly higher when compared with the low-risk patients (5.12% [7/137] versus 1.19% [11/926], respectively; p = .0009). Conclusions: Nuchal translucency (NT) ≥3.0 mm are associated with the highest risk for a CMA abnormality. Submicroscopic chromosomal abnormalities should be accessed when the fetus was found to be with increased NT and normal karyotype. It is, therefore, important to inform parents in a professional prenatal counseling setting regarding the potential advantages of CMA.